Analysis of structural flexibility potential: the case of a cooperative - Felype Neis, Dyogo; Soares, Marison Luiz; Pereira, Mauricio Fernandes (Revista de Administração da UFSM, 2015)
The article aims to analyze the structure flexibility potential of a Medical Cooperative from the perspective of Dominant Coalition. It is characterized as a qualitative research, with the descriptive objective and delineated by the single case study strategy. The data were collected through semi-structured interviews, document analysis and systematic direct observation. It was found that the environment that the Cooperative operates is dynamic and complex, mainly due to the market being regulated by Government, the entry of new competitors, as well as social, cultural and economic factors that underlie any market. This context tends to require greater flexibility potential of organizations. The structural flexibility is associated with the degree of mechanistic: the more mechanical, less flexible. However, even acting in this context and being set up as a cooperative, research indicates the predominance of mechanistic aspects. The cooperative management model, the size of the organization and the use of the Total Quality Management, are aspects that restrict the potential for structural flexibility of Cooperative.